KORELASI KONSEP AURAT DAN KESEHATAN DALAM PERSPEKTIF AL-QUR’AN SURAH AL-NUR: 31 - Suhartini; Windy Widiyati (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2023)
Allah commands Muslim women to cover their aurat except for the face and palms of their hands. This command is to protect women and society. However, there are still many Muslim women who do not cover their aurat properly, leading to various problems in both health and social aspects. This study aims to convey the wisdom from a health perspective based on the Quran, Surah al-Nur verse 31, which allows women to reveal their faces and palms. The method used in this study is qualitative research with a literature review approach. This research explains that the obligation to cover the aurat is not only to maintain faith and piety for women but also has health benefits. There are at least three health benefits that can be obtained, namely physical, mental, and social health. By covering the aurat, women can achieve physical health by protecting their bodies from dust, bacteria, and dirt, thus avoiding various diseases. The mental and social health benefits obtained are that a Muslim woman with a healthy mindset will willingly obey Allah's commandments. Socially, this will contribute to a harmonious community life.